Comics for Literacy in MI Asih Putera: A Sequential Explanatory Study in Elementary Education - Muhamad Rizaldy Waluya; Angga Hadiapurwa; Yayu Wulandari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
Although the pedagogical benefits of comics have been widely proven, attention to the operational aspects needed to support visual literacy strategies in resource-limited environments remains minimal. This study aims to analyze the gap between students' visual literacy preferences and the availability of school library resources at MI Asih Putera using the Dual Coding Theory. Using a sequential explanatory mixed-methods design, this study integrates survey data from 30 students in grades 3-5 with in-depth interviews with the principal, teachers, and librarians. Quantitative findings reveal a disconnect where, despite students' high preference for comics (73%) and interest in physical facilities reaching 93%, there is a sharp gap where 93% of students report unmet needs, particularly in library collection availability, as well as minimal interaction with librarians (13%). The qualitative phase explains that although comics successfully serve as a strategic cognitive hook, library services fail to keep pace with this need due to structural barriers, including a phased procurement budget system, irrelevant book donations, and administrative burdens stemming from manual library management. This study concludes that schools' operational capacity hampers the success of visual literacy strategies. To overcome this, the study recommends cost-effective transformations, such as adopting open-source library automation to ease administrative workload, using open-access e-comics displayed on classroom projectors to address hardware deficits, and formalizing comics into the curriculum to ensure budgetary priority.